CRISPR in animals and animal models - Torres-Ruiz, Raul; Roguez-Perales, Sandra (Progress in molecular biology and translational science, 2017)
CRISPR in Animals and Animal Models, Volume 152, the latest release in the Progress in Molecular Biology and Translational Science series, explores the genome editing CRISPR system in cells and animal models, its applications, the uses of the CRISPR system, and the past, present and future of CRISPR genome editing. Topics of interest in this updated volume include a section on CRISPR history, The genome editing revolution, Programming CRISPR and its applications, CRISPR Delivery methods, CRISPR libraries and screening, CRISPR investigation in haploid cells, CRISPR in the generation of transgenic animals, CRISPR therapeutics, and Promising strategies and present challenges.